2017
DOI: 10.1016/j.bjm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Goat umbilical cord cells are permissive to small ruminant lentivirus infection in vitro

Abstract: Small ruminant lentiviruses isolated from peripheral blood leukocytes and target organs can be propagated in vitro in fibroblasts derived from goat synovial membrane cells. These cells are obtained from tissues collected from embryos or fetuses and are necessary for the establishment of the fibroblast primary culture. A new alternative type of host cells, derived from goat umbilical cord, was isolated and characterized phenotypically with its main purpose being to obtain cell monolayers that could be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…In the present study, results from nPCR and Western Blot demonstrated the occurrence of SRLV-positive neonates from mothers infected by these viral agents. These results were confirmed via cell culture, and observation of syncytia and cell destruction, which are some of the main cytopathic effects characteristic of SRLV evidenced in the literature [20,26,32,33].…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, results from nPCR and Western Blot demonstrated the occurrence of SRLV-positive neonates from mothers infected by these viral agents. These results were confirmed via cell culture, and observation of syncytia and cell destruction, which are some of the main cytopathic effects characteristic of SRLV evidenced in the literature [20,26,32,33].…”
Section: Discussionsupporting
confidence: 74%
“…Hence, the data obtained in this study performed with co-culture of SC of colostrum and SC of milk and OTE cells after use of ethanolic extracts of A. indica and M. azedarach may reveal a possible antiviral activity against CLV. This fact was observed mainly in the organic fraction of ethyl acetate, with an action time of 90 min, with marked inhibition of syncytium formation and cell destruction, which are considered the main characteristic cytopathic effects of CVL elucidated even in previous research studies, where the adoption of a qualitative evaluation through the visualization of their occurrence levels in cultured cells is standard 19,[42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 95%